2017
DOI: 10.1002/jlb.3ma0517-194rr
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the sympathetic nervous system modulates neutrophil function

Abstract: One sentence summary: Sympathetic activation of neutrophils significantly impairs several critical host defense functions, including chemotaxis, phagocytosis and neutrophil-endothelial cell interactions. AbstractEmerging evidence has revealed that noradrenaline (NA), the main neurotransmitter of the sympathetic nervous system (SNS), regulates a variety of immune functions via binding to adrenergic receptors present on immune cells. In this study, we examined the role of NA in the regulation of neutrophil funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
38
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 62 publications
(119 reference statements)
2
38
0
1
Order By: Relevance
“…A recent study has shown that neutrophils from the mouse bone marrow have an impaired chemotactic ability poststroke in an in vitro model. 9 However, neutrophil infiltration to the lungs was observed in both spontaneous-or aspiration-induced pneumonia following tMCAO. 3,5 We observed an increase in alveolar macrophages and the infiltration of neutrophils in the lungs following tMCAO, but their bacterial clearance capability remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent study has shown that neutrophils from the mouse bone marrow have an impaired chemotactic ability poststroke in an in vitro model. 9 However, neutrophil infiltration to the lungs was observed in both spontaneous-or aspiration-induced pneumonia following tMCAO. 3,5 We observed an increase in alveolar macrophages and the infiltration of neutrophils in the lungs following tMCAO, but their bacterial clearance capability remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggested that alterations in the pulmonary immune cell niche following ischemic stroke may partly explain the lung‐specific immunodeficiency. A recent study has shown that neutrophils from the mouse bone marrow have an impaired chemotactic ability poststroke in an in vitro model . However, neutrophil infiltration to the lungs was observed in both spontaneous‐ or aspiration‐induced pneumonia following tMCAO .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Immune cells sense and integrate information from diverse environmental cues (1)(2)(3). In response to physiologic and psychologic stressors, fibers of the peripheral sympathetic nervous system release catecholaminergic stress hormones including norepinephrine into major organ systems to induce a "fight-or-flight" response; epinephrine is released from the adrenal gland into circulation (4,5). Norepinephrine and epinephrine bind to b-adrenergic receptors (b-ARs) to mediate changes in immune cell function.…”
mentioning
confidence: 99%